Off-pump minimally invasive coronary artery bypass grafting in patients with left ventricular dysfunction: the lampang experience - Ushioda, Ryohei; Hirofuji, Aina; Yoongtong, Dit; Sakboon, Boonsap; Cheewinmethasiri, Jaroen; Kamiya, Hiroyuki; Arayawudhikul, Nuttapon (Frontiers in Surgery, 2024)
Introduction The minimally invasive cardiac surgery off-pump coronary artery bypass (MICSOPCAB) is technically difficult; therefore, previous studies have indicated that MICSOPCAB should be contraindicated in patients with impaired left ventricular (LV) function. In this study, we investigated the feasibility of MICSOPCAB in patients with impaired LV function. Methods The 226 patients underwent MICSOPCAB between August 2017 and September 2022. Our study defined impaired LV function as ejection fraction (EF) in echocardiography 40% or less. The patients were divided into Low EF group (n = 39) and Normal EF group (n = 187). Results The Low EF group was in a more critical preoperative condition than Normal EF group (41.0% in the Low EF group vs. 14.4% in the Normal EF group; p < 0.001). For preoperative transthoracic echocardiography, LV end-diastolic diameter (5.5 ± 0.9 cm in the Low EF group vs. 5.0 ± 0.8 cm in the Normal EF group; p < 0.001) and LV end-systolic diameter (4.4 ± 1.0 cm in the Low EF group vs. 3.4 ± 1.0 cm in the Normal EF group; p < 0.001) were significantly larger in the Low EF group. No differences were found in the operative time (180 [160–240] min in the Low EF group vs. 205 [165–253] min in the Normal EF group; p = 0.231) and the median number of distal anastomoses (2 [1–2] in the Low EF group vs. 2 [1–3] in the Normal EF group; p = 0.073). Intensive care unit stay was longer in the Low EF group than in the Normal EF group (2 [1–2] in the Low EF group vs. 1 [1–2] in the Normal EF group; p = 0.010). Perioperative transfusion was more common in the Low EF group than in the Normal EF group (69.7% vs. 49.2%; p = 0.023). There were no differences in major complications, hospital stay, and 30-day mortality. The Kaplan–Meier curve showed no significant difference in postoperative major adverse cardiac or cerebrovascular events rates between the two groups (p = 0.185) Conclusion In this study, MICSOPCAB can be performed in patients with low EF having short- and mid-term outcomes similar to patients with normal EF. Therefore, low EF should not be contraindicated in MICSOPCAB.